Diagnostic dilemma in female genital tract tuberculosis: A case report - Aalok Kumar Yadav; Anamika Jha; Benu Lohani; Santoshi Yadav; Abhikanta Khatiwada (Radiology Case Reports, 2024)
Female genital tract tuberculosis presents a diagnostic challenge because of its variable clinical presentation and radiological manifestation. Most patients are present with history of infertility, pain in the abdomen, vaginal discharge, and bleeding. These symptoms mimic those of gynecological cancer, such as endometrial carcinoma. Endometrial cancer typically manifests with vaginal bleeding in the post-menopausal age group; however, in less than 10% to 20% patients, it can occur in perimenopausal age groups, which makes it difficult to distinguish between malignancy and tuberculosis. We present a case report of a 40-year-old woman who complained of vaginal bleeding and lower abdominal pain. Her imaging findings favored the diagnosis of endometrial carcinoma but histopathology revealed tuberculosis.